2021
DOI: 10.3390/biology10070689
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection for End-Use Quality and Processing Traits in Soft White Winter Wheat Breeding Program with Machine and Deep Learning Models

Abstract: Breeding for grain yield, biotic and abiotic stress resistance, and end-use quality are important goals of wheat breeding programs. Screening for end-use quality traits is usually secondary to grain yield due to high labor needs, cost of testing, and large seed requirements for phenotyping. Genomic selection provides an alternative to predict performance using genome-wide markers under forward and across location predictions, where a previous year’s dataset can be used to build the models. Due to large dataset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 72 publications
4
32
1
1
Order By: Relevance
“…The GS models could be retrained by incorporating data from additional environments in subsequent years. High prediction accuracies for stability could better predict the performance of genotypes at multiple locations during breeding cycles [82].…”
Section: Accuracy For Predicting Gpc and Gpc Stabilitymentioning
confidence: 99%
“…The GS models could be retrained by incorporating data from additional environments in subsequent years. High prediction accuracies for stability could better predict the performance of genotypes at multiple locations during breeding cycles [82].…”
Section: Accuracy For Predicting Gpc and Gpc Stabilitymentioning
confidence: 99%
“…A previous study from our group showed that GS accuracies varied from 0.27 to 0.81 for 14 end-use quality traits using nine different uni-trait models (Sandhu et al, 2021c). Statistical models used for training the uni-or multi-trait GS models play an important role in evaluating performance (Jia and Jannink, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chaetomium globosum is a biocontrol agent which has been found effective against a large number of plant pathogens operating through various mechanisms, such as mycoparasitism, antibiosis, nutrient competitiveness, and inducing systemic resistance in plants (Soytong et al, 2001 ; Sandhu et al, 2021a ). The induced resistance mechanism of C. globosum is least explored except a few reports stating the effectiveness of induced resistance in wheat against tan spot and spot blotch diseases (Istifadah and McGee, 2006 ; Biswas et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chaetomium globosum is a biocontrol agent which has been found effective against a large number of plant pathogens operating through various mechanisms, such as mycoparasitism, antibiosis, nutrient competitiveness, and inducing systemic resistance in plants (Soytong et al, 2001;Sandhu et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%